Improvement of Formability of AISI 1006 Sheets by Hydroforming with Die in Square Deep Drawing - Adil Jaber; Adnan Mohammed; Karem Younis (Engineering and Technology Journal, 2023)
An effort has been made to improve the formability of (1006) AISI steel alloy sheets in deep drawing of square-shaped parts with flat bases through hydroforming. To achieve this goal, the manufacturing process involved the use of a newly developed experimental setup for sheet hydroforming with a die, which was created by the researchers. The key design features of this setup aimed for simplicity and modularity, allowing for potential utilization with oil pressures of up to 100 MPa. The obtained results were compared with those of conventional deep drawing. Both processes were examined under specific conditions to form identical cups up to the full depth of the provided die. Indicators of formability considered for comparison included the minimum possible corner radius, the maximum achievable depth without failure, and the maximum percentage of thinning at the corners. This study demonstrates that hydroforming can enhance the formability of low-carbon steel alloy sheets by improving the flow of metal into the die cavity and reducing thinning at critical regions, when compared to conventional deep drawing processes. In conventional deep drawing, only 70% of the full depth could be achieved before failure due to high local deformations resulting in significantly higher thinning at the corners.